Early historical illustrations of West and Central African music - Hirschberg, Walter (International Library of African Music, 1969)
Early pictorial documents are generally considered to have a controversial ethnographic source value, but it can be shown in individual cases that detailed analysis of such documents often reveals new historical insights and may also be of interest to ethno- musicology.
Keywords: Africa; Musical instruments; Ethnomusicology; African Music